The Quality of Work Life in School and Its Effect on the Teachers’ Performance - Amelia Lalompoh; Moerjati Moerjati; Adya Hermawati; Rahayu Puji Suci; Nasharuddin Mas (Publisher of Widyagama University of Malang (UWG Press), 2019)
The aim of this research is to analyze the effect of work lifequality on the teachers’ performance, the relation between the role of school principal’s management and the teachers’ emotional intelligence affecting the quality of work life. The research was carried out by using a quantitative approach and was through survey method which was based on the structural questionnaire. There were 33 Senior High School teachers of Adventist Colleges in East Java interviewed to obtain variables in answeringthe research objectives. Data were collected in the ordinal form of the Likert scale, described and worked out by using path analysis method based on the framework model formulated. The results show that the quality of work life plays an important role in maximizing or supporting teachers’ performance. It was also found that the school principal’s management competency and the teachers’ emotional intelligence have a great contribution to theteachers’ performance. The quality of work life further functions significantly as the intervening variable effect of the school principal’s management competency and the teachers’ emotional intelligence on teachers’ performance. JEL Classification: I29, J24, M54